2004
DOI: 10.1086/502467
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Serratia marcescens Infections in a Neonatal Intensive Care Unit

Abstract: PFGE analysis showed three independent clusters. Several factors contributed to spread of the epidemic strains: (1) there were many severely premature and susceptible neonates, (2) the NICU was overcrowded during the clusters, and (3) transmission was likely to occur via the hands of staff. Cohorting and improvement of routine infection control measures led to the cessation of each cluster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 30 publications
(19 reference statements)
2
25
0
Order By: Relevance
“…From these pediatric nosocomial infection studies, many environmental sources or point sources have been found as reservoirs for S. marcescens, including hands of health care workers and exposure to health care workers (14,156,198,249,267,362,393,396,423), contaminated breast milk, formula, and breast pumps (133,156,204,274,393), contaminated parenteral nutrition (18), an infected neonate as the index patient or colonization of hospitalized infants (28,63,100,148,238,269,270,275,338,362,400), equipment such as incubators (28,198), laryngoscopes (95,204), suction tubes, soap dispensers (52), and waste jars (393), air conditioning ducts (387), contaminated hand brushes (7), contaminated disinfectants and soap (14,52,76,258,313,396), cotton wool pads (137), multidose nebulizer dropper bottles (215), and multidose medications (133).…”
Section: S Marcescensmentioning
confidence: 99%
See 1 more Smart Citation
“…From these pediatric nosocomial infection studies, many environmental sources or point sources have been found as reservoirs for S. marcescens, including hands of health care workers and exposure to health care workers (14,156,198,249,267,362,393,396,423), contaminated breast milk, formula, and breast pumps (133,156,204,274,393), contaminated parenteral nutrition (18), an infected neonate as the index patient or colonization of hospitalized infants (28,63,100,148,238,269,270,275,338,362,400), equipment such as incubators (28,198), laryngoscopes (95,204), suction tubes, soap dispensers (52), and waste jars (393), air conditioning ducts (387), contaminated hand brushes (7), contaminated disinfectants and soap (14,52,76,258,313,396), cotton wool pads (137), multidose nebulizer dropper bottles (215), and multidose medications (133).…”
Section: S Marcescensmentioning
confidence: 99%
“…As in outbreaks that have occurred in adults, genotyping methods have been used in many pediatric outbreaks to type the involved S. marcescens strains, including sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis of disrupted S. marcescens cells (116), plasmid profiling (18,41,157,258), PFGE (52,190,228,239,269,270,309,313,338,341,366,396), ribotyping (150), rep-PCR (239, 393), RAPD-PCR (18), and PCR fingerprinting (366). Voelz and others performed a systematic analysis of several pediatric S. marcescens outbreak studies from 1984 to 2010 that utilized typing procedures to determine clonality.…”
Section: S Marcescensmentioning
confidence: 99%
“…Some months after the outbreak, two new NI (18 and 19 samples, Figure 1) were observed, but they were controlled. Future outbreak control measures should concentrate on the intensity of colonization, not only of the neonates, but also of the mothers and HWCs 1,14,15 . The antibiotic use and prophylaxis in mothers should be evaluated on a case-by-case basis, thus limiting the potential for broad-spectrum antibiotics to select multiresistant Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to transmission via the hands of staff, 24,[26][27][28][29] pathogens may also spread from inanimate point sources. An increased role for environmental sources has indeed been documented for S marcescens and P aeruginosa, as compared with other pathogens.…”
Section: Discussionmentioning
confidence: 99%